Communicative Learning Approach (Al-Madkhal Al-Ittishali) in Arabic Learning in Madrasah Ibtidaiyah - Mariyatul Qibtiyah, Mayada (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2024)
There are various approaches to learning Arabic, namely the formal approach (al-madkhal al-rasmi), the functional approach (al-madkhal al-wadzifi), the integral approach (al-madkhal al-mutakamil), the sociolinguistic approach (al-madkhal al-ijtima’ial-lughawi), psychological approach (al-madkhal al-nafsiy), psycholinguistic approach (al-madkhal al-nafsiyal-lughawi), behavioristicapproach (al-madkhal al-sulukiy), and communicative approach (al-madkhal al-ittishali). in this journal we will describe the communicative approach (al-madkhal al-ittishali). Classroom activities are marked in a real and dominant way by communication activities, not manipulative exercises and meaningless imitations.